Role of Emotional Intelligence in EFL Learners’ Speaking Accuracy and Fluency (Eurasian Journal of Learning and Academic Teaching, 2025)
This study examines the relationship between emotional intelligence and speaking English as a foreign language among 240 intermediate-level learners from six universities. Participants completed an emotional functioning inventory and underwent a standardized speaking assessment measuring accuracy and fluency. The results show significant positive correlations between emotional intelligence and the components of speaking ability: self-awareness (r=0.67, p